Effects of Multiconstituent Tides on a Subterranean Estuary With Fixed-Head Inland Boundary - Yu, Xiayang; Xin, Pei; Shen, Chengji; Li, Ling (Frontiers in Environmental Science, 2021)
While tides of multiple constituents are common in coastal areas, their effects on submarine groundwater discharge (SGD) and salinity distributions in unconfined coastal aquifers are rarely examined with the exception of a recent study, which explored such effects on unconfined aquifers with fixed inland freshwater input. For a large proportion of the global coastline, the inland areas of coastal aquifers are topography-limited and controlled by constant heads. Based on numerical simulations, this paper examined the variation of SGD and salinity distributions in coastal unconfined aquifers with fixed-head inland boundaries at different distances from the shoreline (i.e., 50, 100, 150 and 200 m). The results showed that the fluctuation intensity of freshwater input was enhanced as the inland aquifer extent decreased, e.g., the range of tide-induced fluctuations in freshwater input increased by around 5 times as the inland aquifer extent decreased from 200 to 50 m. The frequency spectra of the fluctuations of SGD and salinity distributions showed that the coastal aquifer of a shorter inland aquifer extent smoothed out fewer high-frequency tidal constituents but enhanced interaction among different tidal constituents. The interaction among tidal constituents generated new low-frequency signals in the freshwater input and salinity distributions. Regressions based on functional data analysis demonstrated that the inland freshwater input and salinity distributions at any given moment were related to the antecedent (previous) tidal conditions weighted using the probability density function of the Gamma distribution. The influence of the antecedent tidal conditions depended on the inland aquifer extent.